Diversity in Leadership: Australian women, past and present - Damousi, Joy; Rubenstein, Kim; Tomsic, Mary (ANU Press, 2014)
Diversity in Leadership: Australian women, past and present provides a new understanding of the historical and contemporary aspects of Indigenous and non-Indigenous women's leadership in a range of local, national and international contexts.